Biological Effective of organic solvent extracts of Mirabilis jalapa Leaves in the Non-cumulative for mortality of Immature stages Culex quinquefasciatus Say( Diptera : Culicidae ) - Wassen ali; Mohammed R.Annon (Al-Qadisiyah Journal of Pure Science, 2020)
The present research evaluated the efficacy of organic solvent extracts (hexane, ethyl acetate, ethyl alcohol) separately using ppm (0,100,250, 500,1500, 1000, 2000) concentrations of Mirabilis jalapa leaves in the non-cumulative moetality of immature stagesof Culex quinquefaciatus then estimate  LC50 and LC90 by probit analysis. The hexane extract of the leaves M. jalapa of plantwas the most affected in the non-cumulative mortality from that of ethyl acetate and ethyl alcohol. in the non-cumulative mortality of the immature stage . Where LC50 for egg mortality was ppm (2107.7, 2743.5, 3062.7) for hexane extract, ethyl acetate and ethyl alcohol respectively  For the four larval . the first larval stages were the most sensitive of the larval stages of all extracts.The hexan extract was LC50ppm (373.1, 456.2, 758.4, 1941.5) ethyl acetate extract was LC50 ppm (508.1, 673.8, 1369.5, 2745.3) for the four larvae stages respectively. The LC50 for ethyl alcohol extract ppm (511.1, 850.4, 1916.2, 3342.2 ) . In instar pupa the value of LC50 ppm (1993.9, 2183.5, 3562.9) for hexane extract, ethyl acetate and ethyl alcohol respectively.